2015
DOI: 10.1096/fasebj.29.1_supplement.914.2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Intestinal Microbiota and Clinical Characteristics of Patients with Early Stage Breast Cancer

Abstract: Gut microbiota is involved in numerous physiopathological situations including cancers. Our objective is to evaluate the relationship between the composition of microbiota and the clinicobiological characteristics of patients with breast cancer. Clinical data and faeces from 32 patients with early stage breast cancer were collected, before any therapeutic intervention. Bacterial DNA extracted from faeces was amplified by PCR targeting 16S rRNA gene sequences specific to different bacterial phyla. Express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Gut microbiome of breast cancer patients differs from that of healthy subjects and some species contain members that can cause double-stranded DNA breaks in cells that make up breast cancers [ 98 , 99 ]. Furthermore, a correlation has been shown [ 100 ] between composition and cancer grade, suggesting a relationship between the microbiome and breast cancer development and progression. Finally, balancing a dysbiotic microbiome with the use of antibiotics therapy, which usually increases the risk of breast cancer can be useful either before or after a cancer diagnosis [ 96 ].…”
Section: Microbiome and Oral Cancer Prognosismentioning
confidence: 99%
“…Gut microbiome of breast cancer patients differs from that of healthy subjects and some species contain members that can cause double-stranded DNA breaks in cells that make up breast cancers [ 98 , 99 ]. Furthermore, a correlation has been shown [ 100 ] between composition and cancer grade, suggesting a relationship between the microbiome and breast cancer development and progression. Finally, balancing a dysbiotic microbiome with the use of antibiotics therapy, which usually increases the risk of breast cancer can be useful either before or after a cancer diagnosis [ 96 ].…”
Section: Microbiome and Oral Cancer Prognosismentioning
confidence: 99%
“…Other studies also support associations of specific microbial taxa (e.g., Bacteroidetes, Blautia spp.) with breast cancer staging and clinical characteristics, including body size (Bard et al, 2015;Luu et al, 2017). Much less information is available from epidemiologic studies on the possible association between the gut microbiome and breast density.…”
Section: Discussionmentioning
confidence: 99%
“…They collected fecal samples from different stages of breast cancer patients, and performed 16S rRNA sequencing, they found that stage I patients had a lower absolute number of Blautia sp. than stage III, several other bacterial species (Bifidobacterium, Blautia, F. Prausnitzii, and Blautia) were different according to different clinical stages of breast cancer (53). Another research also found that gut microbiota was associated with different stages of breast cancer, compared to patients in stage 0/I, the number of Bacteroidetes, Clostridium coccoides cluster, Clostridium leptum cluster, Faecalibacterium prausnitzii, and Blautia sp.…”
Section: Gut Microbiota and Other Types Of Cancermentioning
confidence: 91%